CONCILIAÇÃO JUDICIAL TRABALHISTA: o “jeitinho” brasileiro e o paradoxo de uma Justiça eficiente entre a produtividade e o desconhecimento da Integridade do Direito - AQUINO JÚNIOR, José Maria de (2016)
This research deals with the labor court conciliation as an alternative means of conflict resolution in individual labor disputes in labor courts. The reconciliation, at first glance, seems to represent an indispensable virtue for life in society; an effective mechanism to resolve conflicts expeditiously, to provide social peace; in short: a process in which everyone. wins. This virtuous vision is presented by the Courts and the National Council of Justice (CNJ) and defended for most of the doctrine, being taken as "truth" by society in general. The purpose of the work is to confront this view, as there is reason to believe that the reconciliation can also represent a major obstacle to building a just and egalitarian society, especially with regard to labor relations. It is therefore necessary to address the following questions: is reconciliation, then the "methodological" institutionalization of the famous "Brazilian way" in courtrooms throughout Brazil? It would be official recognition of a compromise, the flexibility between the law and the situation to which it should apply, subordinating to the people that she should obey? The study uses the dialectic method by means of which carries a multidisciplinary analysis of the object. Taking into account its various dimensions, research involving the various characters of reconciliation: workers, employers, lawyers, judges. From a theoretical framework built through bibliographic research and application of instruments of empirical research, this work shows the evolution of reconciliation in national law, its characteristics, the reasons for each character, its effects and its political and cultural relationship with Brazilian society. The labor court conciliation is, above all, a successful strategy to make the invisible social conflict and to solve it only in appearance, through the logic of the "Brazilian way.